2010
DOI: 10.1111/j.1540-8167.2010.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Extracellular Matrix Remodeling in Dogs with Right Ventricular Apical Pacing

Abstract: LV dyssynchrony by RV apical pacing elicits heterogeneous ECM remodeling in the LV. These findings assist in the elucidation of the pathophysiology of LV desynchronization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
(58 reference statements)
2
24
0
Order By: Relevance
“…Pacing caused significantly abnormal motion at the pacing site, and this pacing-induced dyssynchrony of left ventricle contraction was sufficient to stimulate matrix metalloproteinase-9 (MMP-9) activity. Lin et al [10] have found increased interstitial fibrosis and fragmentation of myofibrils in the left ventricle lateral wall in the right ventricle apical pacing group. Moreover there was increased activation of MMP-2, MMP-9, tissue inhibitor of matrix metalloproteinase TIMP-1 and TIMP-3 in the same area.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pacing caused significantly abnormal motion at the pacing site, and this pacing-induced dyssynchrony of left ventricle contraction was sufficient to stimulate matrix metalloproteinase-9 (MMP-9) activity. Lin et al [10] have found increased interstitial fibrosis and fragmentation of myofibrils in the left ventricle lateral wall in the right ventricle apical pacing group. Moreover there was increased activation of MMP-2, MMP-9, tissue inhibitor of matrix metalloproteinase TIMP-1 and TIMP-3 in the same area.…”
Section: Introductionmentioning
confidence: 98%
“…Though, it is highly probable that the diastolic dysfunction, observed in this study, can be mainly attributed to rapid pacing-induced ischemia, and not to direct effect of pacing. Nevertheless, two animal experiments provide probable pathophysiologic explanation for the immediate relation of pacing and left ventricle dysfunction [9,10]. Garcia et al [9] used piezoelectric sensors, that were located at pacing site and remote site, to assess myocardial contractility.…”
Section: Introductionmentioning
confidence: 99%
“…There are several papers elucidating the underlying mechanisms of detrimental effect of right ventricle apical pacing [6][7][8]. Tse et al [8] have proved that patients with right ventricle apical pacing have had significantly increased perfusion defects in dipyridamole thallium myocardial scintigraphy along with regional wall motion abnormalities in radionuclide ventriculography.…”
Section: Detrimental Effect Of Pacing-underlying Mechanismsmentioning
confidence: 99%
“…The animal experimental models [6,7] provide much more detailed characteristic of consequences of pacing. Both experiments were carried out in dogs, but researchers have studied different pacing sites.…”
Section: Detrimental Effect Of Pacing-underlying Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation